Security-Reliability Tradeoff Analysis for Multiuser FSO Communications Over a Generalized Channel - Wafaa Mohammed Ridha Shakir; Jinan Charafeddine; Hani Hamdan; Israa Ali Alshabeeb; Nidaa Ghalib Ali; Israa E. Abed (IEEE Access, 2023)
The security-reliability tradeoff (SRT) in free-space optical (FSO) communications is the most critical property to highlight, especially with respect to the development of wireless optical communications. In this paper, opportunistic scheduling selection techniques are used to improve the SRT of multiuser FSO systems under the combined influence of atmospheric turbulence with Fisher-Snedecor $\mathcal {F}$ distribution, generalized pointing error, and path losses due to foggy weather. Due to the broadcast nature of wireless optical propagation, the optical transmission from the transmitting users to the legitimate receiver can be easily intercepted by eavesdroppers. Therefore, an optimal user scheduling (OUS) scheme is proposed in this work to protect the legitimate wireless transmission from eavesdroppers, where a user with the highest secrecy capacity is scheduled to transmit his confidential information to the receiver. Closed-form expressions for the outage probability, interception probability, and SRT are derived for the conventional round-robin scheduling (RRS) and the proposed OUS. In addition, an asymptotic analysis for the outage probability, interception probability, and SRT is performed to provide insight into the impact of user scheduling on the system performance. We also propose the use of “friendly jamming” techniques, where the user with the lowest secrecy capacity is selected by the authorized receiver to jam the existing interceptor. Finally, another SRT is formulated to determine the impact of a friendly jammer on the secrecy performance of the system. The results show that the proposed OUS outperforms the RRS in terms of intercept probability and SRT performance. The obtained exact and asymptotic results are validated by Monte-Carlo simulations.